1998
DOI: 10.1007/s002689900401
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in Inflammatory Bowel Disease

Abstract: Cytokines play a central role in the modulation of the intestinal immune system. They are produced by lymphocytes (especially T cells of the Th1 and Th2 phenotypes), monocytes, intestinal macrophages, granulocytes, epithelial cells, endothelial cells, and fibroblasts. They have proinflammatory functions [interleukin-1 (IL-1), tumor necrosis factor (TNF), IL-6, IL-8, IL-12] or antiinflammatory functions [interleukin-1 receptor antagonist (IL-1ra), IL-4, IL-10, IL-11, transforming growth factor beta (TGF beta)].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
355
1
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(375 citation statements)
references
References 88 publications
12
355
1
7
Order By: Relevance
“…The results point to a continuous activation of monocytes/macrophages in the course of IBD and correspond to other results (Hyun and Mayer 2006;Rogler and Andus 1998). Nevertheless, the causal factors beyond the activation of the cells are incompletely understood, although experiments on animal models provide evidence for the importance of antigens of commensal bacteria in stimulation of the mucosal immune system (Rennick and Fort 2000;Sartor 2004).…”
Section: Discussionsupporting
confidence: 80%
“…The results point to a continuous activation of monocytes/macrophages in the course of IBD and correspond to other results (Hyun and Mayer 2006;Rogler and Andus 1998). Nevertheless, the causal factors beyond the activation of the cells are incompletely understood, although experiments on animal models provide evidence for the importance of antigens of commensal bacteria in stimulation of the mucosal immune system (Rennick and Fort 2000;Sartor 2004).…”
Section: Discussionsupporting
confidence: 80%
“…But, contrary to those reports where autophagy acts as a suicidal mechanism, 55,56 our results suggested that the major purpose of the accompanying increase in autophagy observed during inflammation is to fully activate Akt1, a major antiapoptotic signaling molecule. 16 However, the continuous cytokine stimulation of the inflamed mucosa 57,58 might result in the dysregulation of the machinery that controls Akt signaling pathway, leading to uncontrolled Akt activation and cell death. This is a plausible scenario because proinflammatory cytokines can also affect other biological processes that control Akt function such as protein synthesis 2 and/or Akt targeting/shuttling, 2 which is known to be important for controlling Akt destiny and function.…”
Section: Discussionmentioning
confidence: 99%
“…On microscopy, material from patients with pancolitis and patients with left-sided colitis differed principally in the degree of inflammation present (data not shown). Patients with IBD have a disturbed balance between pro-and anti-inflammatory cytokines in the mucosa, one possible reason why anticytokine treatment is efficient (Rogler and Andus, 1998), and the production of proinflammatory cytokines is higher in severe UC colitis than in colitis with lesser endoscopic grades of inflammation (Ishiguro, 1999;Raddatz et al, 2005). In our study, mRNA expression levels of iNOS, which in pancolitis is expressed after induction by certain cytokines, microbes, and bacterial products (Kolios et al, 2004), were significantly increased (15-fold), higher than in left-sided colitis (Table 5).…”
Section: Discussionmentioning
confidence: 99%